Natural Products with Analgesic Effect from Herbs and Nutraceuticals Used in Traditional Chinese Medicines - Wang, Tian-Xing; Wu, Guo-Jie; Jiang, Jian-Guo (Current Molecular Medicine, 2020)
Background: Pain is one of the most common clinical symptoms . This review aims to describe research on herbs and their active ingredients in treating pain and provide a valuable reference for the development and utilization of analgesic traditional Chinese medicine (TCM). Material and Methods: The literature search was performed from 1995 to October 2016, covering the relevant studies that concern the treatment of pain with TCM. Active ingredients extracted from TCM with analgesic activity are summarized and classified into six categories, including polysaccharides, saponins, alkaloids, flavonoids, terpenoids, and other constituents. Results: There are two pathways constituting the analgesic mechanisms of TCM: through the central nervous system and the peripheral nervous system. The former pathway includes increasing the content of endogenous analgesic substances like opiate peptide, cutting down the second messenger of neurotransmitter like nitric oxide (NO), reducing the content of prostaglandin E2 (PGE2) in brain tissues, blocking the central calcium channel, reducing excitatory amino acids in brain tissues, inhibiting their receptors and raising the content of the central 5-hydroxytryptamine (5-HT). The latter one usually involves the decrease in the secretion of peripheral algogenic substances, the induction of pain-sensitive substances, the accumulation of a local algogenic substance, the increase in the release of peripheral endogenous analgesia materials and the regulation of c-Fos gene (immediate early gene).
Keywords: pharmacological mechanisms